Analysys of seismic activity influence on hydrogeological anomalies formation in underground waters (Pinachevo station, east Kamchatka); Творчество юных - шаг в успешное будущее - Efstifeeva A. S. (Доклады на иностранном языке, 2014)
Заглавие с титульного экрана